2021
DOI: 10.21203/rs.3.rs-327912/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutralizing and binding antibody kinetics of COVID-19 patients during hospital and convalescent phases

Abstract: Background: Knowledge of host immune response after natural SARS-CoV-2 infection is essential for the direction of vaccination and epidemiological control strategies against COVID-19.Methods: Thirty-four COVID-19 patients were enrolled with 244 serial blood specimens (38.1% after hospital discharge) collected to explore the chronological evolution of neutralizing (NAb), total (TAb), IgM, IgG and IgA antibody in parallel.Results: IgG titers reached a peak later (35 days postonset) than those of Nab, Ab, IgM and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…To date, few studies have longitudinally examined anti-SARS-CoV-2 antibody levels following convalescence from COVID-19 (Beaudoin-Bussieres et al, 2020;Crawford et al, 2020;den Hartog et al, 2021;Figueiredo-Campos et al, 2020;Gudbjartsson et al, 2020;Ibarrondo et al, 2020;Isho et al, 2020;L'Huillier et al, 2021;Lumley et al, 2021;Roltgen et al, 2020;Sasisekharan et al, 2021;Wang et al, 2020;Wheatley et al, 2021;Wu et al, 2020;Yamayoshi et al, 2021;Yao et al, 2020), and reports have yielded contradictory data concerning the longevity of the antibody response. Waning levels of antibodies against SARS-CoV-2 within several weeks have been reported, including anti-N, anti-S2 (Cterminal subunit of the spike protein), anti-S1 (N-terminal subunit of the spike protein), anti-RBD1 (receptor binding domain), and neutralizing antibodies (Beaudoin-Bussieres et al, 2020;Ibarrondo et al, 2020;Roltgen et al, 2020;Wheatley et al, 2021), with a more rapid decay of anti-N IgG levels compared to anti-S (Wheatley et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, few studies have longitudinally examined anti-SARS-CoV-2 antibody levels following convalescence from COVID-19 (Beaudoin-Bussieres et al, 2020;Crawford et al, 2020;den Hartog et al, 2021;Figueiredo-Campos et al, 2020;Gudbjartsson et al, 2020;Ibarrondo et al, 2020;Isho et al, 2020;L'Huillier et al, 2021;Lumley et al, 2021;Roltgen et al, 2020;Sasisekharan et al, 2021;Wang et al, 2020;Wheatley et al, 2021;Wu et al, 2020;Yamayoshi et al, 2021;Yao et al, 2020), and reports have yielded contradictory data concerning the longevity of the antibody response. Waning levels of antibodies against SARS-CoV-2 within several weeks have been reported, including anti-N, anti-S2 (Cterminal subunit of the spike protein), anti-S1 (N-terminal subunit of the spike protein), anti-RBD1 (receptor binding domain), and neutralizing antibodies (Beaudoin-Bussieres et al, 2020;Ibarrondo et al, 2020;Roltgen et al, 2020;Wheatley et al, 2021), with a more rapid decay of anti-N IgG levels compared to anti-S (Wheatley et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…After infection with SARS-CoV-2, seroconversion usually occurs 7-14 days after diagnosis (Krajewski et al, 2020;Long et al, 2020a;Peeling et al, 2020;To et al, 2020), with a peak in antibody levels observed around 30-35 days following symptom onset (Crawford et al, 2020;Isho et al, 2020;Wang et al, 2020;Yao et al, 2020). The longevity of the antibody levels and the durability of immunity following a SARS-CoV-2 infection have not yet been fully elucidated due to the short time elapsed since this disease was first recognized, in contrast to the well-studied antibody kinetics during the acute phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, the nAb titer peaks 30 days after symptom onset and declines by 25% every 15 days 17 (largely due to the decline in neutralizing IgM and IgA) 29,30 . It is therefore sounding that the days since positive nasopharyngeal swab correlates with the nAb titer.…”
Section: Discussionmentioning
confidence: 99%
“… 11 13 The latter has been shown in many studies to be likely related to the severity of COVID-19, further emphasizing the significance of knowing this information rather than just the antibody levels. 14 18 …”
mentioning
confidence: 99%